Pengintegrasian Pendidikan Karakter Melalui Pendekatan Pragmatik dalam Pembelajaran Bahasa Indonesia Daring - Sudjalil Sudjalil; Gigit Mujianto; Rudi Rudi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to describe (1) the model of integrating character education in Indonesian language learning, (2) implementing the integration of character education through a pragmatic approach in Indonesian language learning, and (3) implications of the pragmatic approach on the integration of character education in Indonesian language learning. This type of research uses case studies with a qualitative approach. The research subjects were Teacher Professional Education students in the Department of Indonesian Language Studies at the Faculty of Teacher Training and Education, University of Muhammadiyah Malang. The research data are in the form of speech data and field note data, which are sourced from face-to-face verbal interactions between teachers and students in the learning process in the classroom, with data collection techniques using observation and documentation. The data analysis technique is the Milles & Huberman model. The results showed that: (1) the model of integrating character education in Indonesian language learning through the pragmatic approach used by the teacher is the illocutionary model; (2) the implementation of the integration of character education through a pragmatic approach in learning Indonesian is the process of communication between teachers and students based on the principle of cooperation; and (3) the implication of the pragmatic approach to the integration of character education in Indonesian language learning is the emergence of three components of good character.